EFEKTIVITAS PENGELOLAAN ALOKASI DANA DESA PADA DESA DEDEKADU KECAMATAN LOLI KABUPATEN SUMBA BARAT - Siregar, Kodir (Jurnal Politik Pemerintahan Dharma Praja, 2018)
This research is purpose to understand (1) the effectiveness management village funds allocation in Dedekadu village in years 2012-2017, (2) obstacles that faced in realization village funds allocation in Dedekadu village, (3) cope with the obstacles in realization village funds allocation in Dedekadu village. The design is descriptive research. Data were collected with the documentation and interview. The result showed (1) management effectiveness village funds allocation from years 2012-2017 referring to be in category effective. The effectiveness management village funds allocation in Dedekadu villages year 2012 (98,76%), 2013 (96,58%), 2014 (100%), 2015 (99,81%), 2016 (97,29%), dan 2017 (100%). (2) obstacles experienced in realization village funds allocation is the comprehension of human resources remain low, miss communication, and liquefaction the village funds allocation late. (3) cope the obstacles of realization village funds allocation can did with choacing, increase coordination, and make fund reseve.